2019
DOI: 10.1101/636217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrastructure of the axonal periodic scaffold reveals a braid-like organization of actin rings

Abstract: Recent super-resolution microscopy studies have unveiled a periodic scaffold of actin rings regularly spaced by spectrins under the plasma membrane of axons. However, ultrastructural details are unknown, limiting a molecular and mechanistic understanding of these enigmatic structures. Here, we combine platinum-replica electron and optical super-resolution microscopy to investigate the cortical cytoskeleton of axons at the ultrastructural level. Immunogold labeling and correlative super-resolution/ electron mic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 50 publications
3
80
0
Order By: Relevance
“…New improvements in superresolution (Culley, Tosheva, Matos Pereira, & Henriques, ; Wang, Taki, et al, ) and correlative microscopies (Vassilopoulos, Gibaud, Jimenez, Caillol, & Leterrier, ) should soon enable us to capture the dynamic itineraries of ankyrins and spectrins at nanoscale resolution, which will in turn help us more precisely pinpoint their roles in, and individual commitments to, known and novel pathways. This will represent a significant step in deciphering the code behind their modes of functional partitioning and long‐range and local organization.…”
Section: Perspectivesmentioning
confidence: 99%
“…New improvements in superresolution (Culley, Tosheva, Matos Pereira, & Henriques, ; Wang, Taki, et al, ) and correlative microscopies (Vassilopoulos, Gibaud, Jimenez, Caillol, & Leterrier, ) should soon enable us to capture the dynamic itineraries of ankyrins and spectrins at nanoscale resolution, which will in turn help us more precisely pinpoint their roles in, and individual commitments to, known and novel pathways. This will represent a significant step in deciphering the code behind their modes of functional partitioning and long‐range and local organization.…”
Section: Perspectivesmentioning
confidence: 99%
“…Furthermore, F‐actin forms a membrane‐associated periodic lattice together with βII, βIII, and βIV spectrins, where actin filaments are spaced by spectrin tetramers with a periodicity of approximately 190 nm (Bär et al, ; D'Este et al, ; Han, Zhou, Xia, & Zhuang, ). A very recent correlative dSTORM and electron microscopy study indicated that on an ultrastructural level, this periodically organized F‐actin forms a braid‐like structure containing two long, entwined actin filaments (Vassilopoulos, Gibaud, Jimenez, Caillol, & Leterrier, ). It has been suggested by Han et al, that spectrin isoforms partially exhibit a compartmentally distinct expression.…”
Section: Synaptic Actin Cytoskeletonmentioning
confidence: 99%
“…Actin is present in the neuron in various pools like the actinspectrin membrane periodic skeleton (D'Este et al, 2015;Xu et al, 2013), waves (Flynn et al, 2009), trails (Ganguly et al, 2015) and actin-rich regions (Sood et al, 2018;van Bommel et al, 2019). The MPS shows the presence of braided filaments that may arise from complex actin arrangements (Vassilopoulos et al, 2019). However, a detailed description for other structures like actin trails or branched actin at dendritic spines or the actin enrichment seen at the AIS is not well known.…”
Section: Discussionmentioning
confidence: 99%
“…Actin and associated proteins help the neurons withstand compressive forces and maintain neuronal structure through the formation of membrane associated periodic structures (MPS) (Hammarlund, Jorgensen, & Bastiani, 2007;Krieg, Dunn, & Goodman, 2014;Xu et al, 2013). MPS, is a quasione-dimensional periodic lattice structure present under the plasma membrane, comprising of braided ring like actin structures connected by αand β-spectrin heterotetramers (D'Este, Kamin, Gottfert, El-Hady, & Hell, 2015;He et al, 2019;Vassilopoulos, Gibaud, Jimenez, Caillol, & Leterrier, 2019;Zhong et al, 2014). Actin waves form growth-cone-like structures along the shaft of neuronal processes (Flynn, Pak, Shaw, Bradke, & Bamburg, 2009).…”
Section: Introductionmentioning
confidence: 99%